“Sowan” dan Penguatan Pendidikan Karakter Pesantren Berkelanjutan - Rofiq, Ach. (Institut Agama Islam Negeri (IAIN) Tulungagung, 2018)
This article will describe the Kiai as primary leader in Islamic boarding school who has responsibility to teach Islamic doctrine and build good character of santries in one of unique Islamic boarding school traditions “sowan”, that sowan tradition either as medium of kiai-santries relationship empowerment, it become a medium of following character building education. The kiai can encourage and motivate the santries to be consisten and commite in applicate pesantren characters like patients, honest, consisten, and empowering fith to the God in their daily actions in the life. The trust of Kiai’s personality as ultimate figure for them make them obey to their fatwa and advices and believe that aplicate everything that kiai said make them get barokah and usefulness in their life in a middle of communities. So that, that mind set can be a modal for Kiai to empower character building education goin on continuously gradually long time to the santries who have gone out of Islamic boarding school.